Analysis of Consumable Material Inventory Control in Brake System Company - Fahmi, Afiqoh Akmalia; Soraya Putri, Arinda; Setiyawan, Dani (TALENTA Publisher, 2023)
A good raw material and consumables control planning system is important in the production process so that the process runs according to schedule and target. Brake system company is a manufacturing company engaged in brake systems. Concerning the control of consumable material, this company often experiences overstock in warehouses, causing an overrun in inventory costs and investment cannot develop. One of these conditions can be influenced by the ordering method applied by the company which is still not appropriate. The purpose of this study is to find out and provide proposed to companies related to the cost of consumable inventory by comparing the three methods of determining lots based on Fixed Order Quantity (FOQ), Economic Order Quantity (EOQ), and Fixed Order Quantity Proposed (FOQ Proposed) is the FOQ method combined with the Lot for Lot (LFL) principle to determine the method with the most optimal inventory cost. From the results of the study, it is known that the Proposed FOQ method has the lowest total inventory cost compared to the other two methods. The proposed FOQ approach could reduce inventory costs by up to one-third times the previous cost.